Sensitive fluorescence on-off probes for the fast detection of a chemical warfare agent mimic - Senge, Mathias (My University, 2018)
Two highly sensitive probes bearing a nucleophilic imine moiety have been utilized for the selective detection of chemical warfare agent (CWA) mimics. Diethyl chlorophosphate (DCP) was used as mimic CWAs. Both iminocoumarin-benzothiazole-based probes not only demonstrated a remarkable fluorescence ON-OFF response and good recognition, but also exhibited fast response times (10 s) along with color changes upon addition of DCP. Limits of detection for the two sensors 1 and 2 were calculated as 0.065 μM and 0.21 μM, respectively, which are much lower than most other reported probes. These two probes not only show high sensitivity and selectivity in solution, but can also be applied for the recognition of DCP in the gas state, with significant color changes easily observed by the naked eye.
PUBLISHED
cited By 0
Keywords: Fluorescence probe; Chemical warfare agents; Diethyl cholorophosphate; Recognition